BIOCHEMICAL ASSESSMENT OF THE COMBINED USE OF CHITOSAN AND WHEY POWDER FOR MANAGING METABOLIC PROCESSES IN BROILER CHICKENS: AN EXPERIMENTAL RESULTS-BASED APPROACH (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article presents a revised biochemical interpretation of experimental data on the combined use of chitosan and whey powder in broiler chickens. During a 42-day observation period in Ross 308 broilers, live weight dynamics, feed conversion, selected blood biochemical parameters, and the functional condition of the intestinal environment were evaluated. The findings indicate that the combined additive produced a more stable anabolic and sorption-metabolic effect than the separate use of chitosan or whey powder. In particular, the experimental combination group demonstrated an 8-12% higher live weight than the control, a 6-9% improvement in feed conversion, and physiologically favorable shifts in markers related to protein and energy metabolism. These data support the view that chitosan modulates the intestinal environment, whereas whey powder provides rapidly utilizable protein and lactose substrates, resulting in a synergistic metabolic response.